Prioritas Penanganan Kerusakan Jalan Lentur Berdasarkan Tingkat Kerusakan dan Nilai Ekonomi (Studi Kasus : Jalan Gatot Subroto Blora Sta 0+350 – 2+850) - Ristiyanto, Hartono Guntur; Supranoto, Bambang; Khusaini, Fallah (SIMETRIS, 2023)
Determining the priority order for road repairs requires a road damage study to take a complete inventory of road conditions by means of a survey to collect data on pavement conditions. Determining the level of damage and analyzing the economic feasibility of handling road damage based on the survey results is useful for determining the priority order for handling which parts of the road need to be repaired first. Based on the description of the background to the problem, the formulation of the research problem is: how to determine the priority for handling road damage based on the level of road damage and the economic value resulting from repairing the damage? Primary data collection was carried out by surveying road damage using the survey instrument method of Dirgolaksono and Mochtar (1990). Data analysis is divided into 3 parts: road damage analysis, economic analysis using the ND Lea Consultant method, and determining priorities for handling road damage. The results of the identification and analysis of the level of damage per 100 m of road length showed that Jl. Gatot Subroto segment B (west to east traffic direction) has a greater value than the opposite direction. Meanwhile, the BCR, NPV and LHR values ​​for segment A have greater values ​​than segment B. Therefore, the priority for handling road damage is prioritized on segment A first. This research has several limitations related to several assumptions used. The Consumer Price Index (CPI) data used is assumed to be the same as the Kudus Regency CPI due to limited secondary data. In addition, it is necessary to carry out a comparative analysis of the BOK results if a different type of road damage management is used to that used in this research. Likewise, analysis needs to be carried out regarding determining priorities for handling damage per road length/section/road stationing. Method development or improvement needs to be carried out for further research in order to overcome the subjectivity of observations. For example: by using a scoring or weighting method for parameters that influence priority determination by conducting interview surveys with experts or stakeholders related to road construction.